PENGARUH DISIPLIN KERJA, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MTs NEGERI 8 SRAGEN - Nurul Khasib Awalimatul Rohmah; Asih Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to improve performance, employee development, enhance job satisfaction, manage change, and increase retention. The objectives of this study are: 1) to analyze whether work discipline has a positive and significant effect on teacher performance at MTs Negeri 8 Sragen, 2) to analyze whether work communication has a positive and significant effect on teacher performance at MTs Negeri 8 Sragen, and 3) to analyze whether the work environment has a positive and significant effect on teacher performance at MTs Negeri 8 Sragen. Data collection in this research was conducted using questionnaires distributed to all teachers at MTs Negeri 8 Sragen. The sample for this study consisted of 41 teachers. The sampling technique used in this research was saturation sampling. The data analysis technique employed in this study was multiple regression analysis using the SPSS application. The hypothesis results of this study indicate that work discipline does not have a positive and significant effect on teacher performance at MTs Negeri 8 Sragen, while communication and the work environment have a positive and significant effect on teacher performance at MTs Negeri 8 Sragen.